2010
DOI: 10.1073/pnas.0909366107
|View full text |Cite
|
Sign up to set email alerts
|

Engineering cis-telomerase RNAs that add telomeric repeats to themselves

Abstract: Telomerase is a ribonucleoprotein complex consisting of a protein reverse transcriptase (TERT) and an RNA subunit (TR). Telomerase normally adds telomeric DNA repeats to chromosome ends. Here, we engineer human and Tetrahymena cis-telomerase RNAs, each having a DNA primer covalently linked to its 3′ end. We find that cis-telomerase synthesizes DNA with increased repeat addition processivity (RAP) but does not completely rescue the RAP defect of the L14A mutant of Tetrahymena TERT. This supports the conclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…5b). In addition, Qiao et al 32 previously reported that an engineered human cis -telomerase that linked the 3′ end of the telomerase PK region to the 5′ end of the DNA primer with a five-nucleotide linker could generate a near-optimal telomerase activity, thus indicating that the distance between the 3′ end of PK and the 5′ end of DNA primer is ~33 Å. In keeping with this observation, the orientation of PK in our proposed model could allow the 3′ end of PK to be adjacent to the 5′ end of the DNA (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5b). In addition, Qiao et al 32 previously reported that an engineered human cis -telomerase that linked the 3′ end of the telomerase PK region to the 5′ end of the DNA primer with a five-nucleotide linker could generate a near-optimal telomerase activity, thus indicating that the distance between the 3′ end of PK and the 5′ end of DNA primer is ~33 Å. In keeping with this observation, the orientation of PK in our proposed model could allow the 3′ end of PK to be adjacent to the 5′ end of the DNA (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…13 Cancer cells and ESCs express this marker, which indicates the potential for telomerase activators to contribute to the development of tumors. 14 Our finding that AECs did not express TERT suggests that AECs do not form tumors.…”
Section: Discussionmentioning
confidence: 99%
“…TERT is an enzyme that adds DNA sequence repeats (“TTAGGG” in all vertebrates) to the 3' end of DNA strands in the telomere regions, which are found at the ends of eukaryotic chromosomes. 13 Cancer cells and ESCs express this marker, which indicates the potential for telomerase activators to contribute to the development of tumors. 14 Our finding that AECs did not express TERT suggests that AECs do not form tumors.…”
Section: Discussionmentioning
confidence: 99%
“…This region of the pseudoknot is more protected from chemical probing in vivo than the free TR is in vitro (46). An engineered cis-telomerase, in which a 6 nt DNA primer is linked to the 3′ end of the pseudoknot, has its maximal activity with a linker length of 5 nt or longer, which corresponds to a maximal distance of 33 Å between the end of the pseudoknot and the 5′ end of the TR template (47). This result is consistent with the close proximity of the end of the pseudoknot to the template seen in our model structure.…”
Section: Discussionmentioning
confidence: 99%